(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article provides guidelines for memorizing the content of concepts when teaching trigonometric materials to schoolchildren, in particular, two methods for memorizing tabular values of trigonometric functions. There are comments on the benefits of the Trigonometry in the Palm and Diagonal Table method. In addition, the article describes illustrative and cognitive methods and mechanisms of mnemonic movement in the development of logical memory. The role of memorizing mathematical concepts in revealing the mechanism of logical constructions and the development of students’ skills to form and prove mathematical sentences (axioms, statements and theorems) is determined by illustrative and cognitive methods, such as "Trigonometry in the palm of your hand" and "Diagonal table".